HEALTH ISSUES EXPERIENCED BY POST-MENOPAUSAL WOMEN IN RURAL AREA OF TENGNOUPAL DISTRICT, MANIPUR - T. K. MUILUNGDAR MARING; MANJULA G. KADAPATTI (The Journal of Research ANGRAU, 2024)
The study was conducted during the year 2022-23 with an aim to study the health related issues among post-menopausal women in Pallel rural area of Tengnoupal district, Manipur. The sample comprised of a total number of 100 rural women in the age group of 55-60 years from Tengnoupal district, Manipur. A pre-structured interview schedule was used for the purpose of studying the post-menopausal health issues. The findings of the study showed that postmenopausal women respondents had felt and experienced changes in their appearance or tone of skin (100%) followed by suffered from backache or mobility problems (90%), easily forgetting things (67%), changes in health and energy (63%), decrease in physical strength (64%), lesser interest in sexual desire (57%), and difficulty in urinating (21%). The factors, avoidance of intimacy with partner, rate of discomforts/problems faced and feelings of health and energy were found to have an association at 5% level of significance on age of the women. The study showed that these requires some educational programs to enhance their quality of life, better health, wellbeing and wellness.